Orientasi Eksternal, Tanggung Jawab Sosial Perusahaan, dan Emisi Polusi - Aziza, Nurna (Jurnal Akuntansi dan Keuangan, 2024)
Companies in open economies with stronger external orientations have come under pressure from customers and other stakeholders to implement global corporate social responsibility (CSR) activities since the 2000s. The purpose of this study proposes a relationship between CSR, the level of external orientation, and pollution emissions, such as pollution reduction. It uses an empirical methodology using secondary data for manufacturing companies. The results showed that external orientation is related to pollution emissions, corporate social responsibility is negatively related to pollution emissions, and there is a proven moderating effect on pollution emissions. The higher the external orientation but with high corporate social responsibility can withstand the increase in pollution emissions by manufacturing companies.